The impact of personality on academic burnout: a systematic review - Dahamat Azam, Mohamad Naqiuddin; Xiaoyuan, Liu; Arshat, Zarinah (Ani Publishing, 2024)
Purpose: The intricate link between personality traits and academic burnout was explored through a comprehensive search across multiple databases like ScienceDirect, Scopus, PubMed, and PsycINFO. This review primarily delves into the Five-Factor Model of personality to illuminate the complexities of academic burnout. Method: At the outset, an exhaustive search strategy yielded a remarkable 2,230 papers. Subsequently, following meticulous selection criteria, 40 studies underwent systematic analysis. The culmination of this process affirmed the association between specific personality traits and academic burnout. Findings: Review articles indicated that elevated neuroticism levels correlated with heightened academic burnout, while decreased levels of Agreeableness, Conscientiousness, Extraversion, and Openness were also linked to increased burnout levels. These findings underscore the intricate nature of academic burnout, suggesting that specific combinations of personality traits can significantly influence its occurrence. Implications for Research and Practice: These findings carry substantial implications for the academic domain, emphasizing the imperative for educational institutions and policymakers to recognize the influence of personality in formulating strategies to mitigate burnout among academics. Interventions targeting specific personality dimensions hold promise for effective intervention strategies.